PROTOTIPE ALAT PENGUKUR SUHU PANAS (HOT POINT) PADA PERALATAN GARDU INDUK PLN SECARA WIRELESS BERBASIS MIKROKONTROLER ATMEGA 8535 - Angger Raharjanto; Bambang Supradono; Aris Kiswanto (MEDIA ELEKTRIKA, 2013)
Lately, the problem of hot point on substation equipment in PLN be an interesting thing to say. Mainly about heat problem which is uncontrolled and unable to be checked continually, this issue deals with the system’s safety and reliability that happens in the substation To overcome this issue, study on the solution which is by making a prototype device to measure real time temperature or hot point continually and by using wireless has been held. This device uses ATMEGA 8535 and heat sensor TPA 81 then it sends the data bay FM signal and later on, this data can be shown and save in computer Using the prototype, the problem that PLN faces these days can be solved, because this prototype device can monitor the hot point change continually and real time